Naturalizing consciousness: A theoretical framework - Edelman, Gerald M. (The National Academy of Sciences, 2003)
Consciousness has a number of apparently disparate properties, some of which seem to be highly complex and even inaccessible to outside observation. To place these properties within a biological framework requires a theory based on a set of evolutionary and developmental principles. This paper describes such a theory, which aims to provide a unifying account of conscious phenomena.